Utiliza????o de informa????es patent??rias como proposta para otimiza????o da gest??o financeira em um hospital p??blico - Rosa, Leandro Souza (2018)
In Brazil, public institutions must obey the chronological order of payment, as it is a legal determination to execute payment of their expenditures. In this study it was verified that financial resources are not allocated at the time needed, for this reason in some cases the chronological order of the goods is not followed, enabling the supplier that delivered on the 02 of the month, to receive first than the supplier who provided service or delivered some input on day 01. Specific legislation that no creditor should be privileged, except the exceptions published in the official journal. If what has been delivered is in accordance with the agreement entered into between the parties, such obligation shall be paid within thirty days from the certified invoice. As a consequence, the chronological order of payment may cause financial loss to the treasury, the institution's exposure, non-approval of accounts for the fiscal year, imprisonment and not release of the managers. Patent information has the potential to solve problems of a variety of natures, including those associated with Public Hospital Financial Management, leveraging efficiency and productivity. Patents that are not protected in Brazil can be replicated in full with the minimum financial allocation. Bases without references such as Espacenet have underutilized information that, however, can not be evaluated manually due to the enormous amount of documents available, and it is necessary to use data mining tools. For this reason, we proposed the use of the Patent2net computational tool as a medium for the selective mining of patents in the Espacenet world database, which has more than 100 million patent documents filed, being part of them unprotected in Brazil, and which may contribute to implement improvements in the administration of public hospitals. This research fits as a quantitative, descriptive, exploratory and technometric analysis. With the execution of Patent2net, 618 patents were identified with the possibility of minimizing the chronological order of payments. This research also showed that both Brazilian companies and Brazilian researchers do not participate in the development of this type of technology, denoting the need for greater investments in this area.